Action sharpens sensory representations of expected outcomes - Daniel Yon (Nature Portfolio, 2018)
Our brains predict the likely sensory consequences of actions we take; one theory is that these sensory responses are suppressed, but another theory is that they are sharpened. Here, the authors show using fMRI evidence consistent with the sharpening account for sensory consequences of hand movements.